Islamic Economic Literacy, Digital Access, and ZIS Awareness: The Mediating Role of Religiosity - Emiliana; Reni Helvira; Bahrul Ulum (Universitas Airlangga, 2024)
The purpose of this study was to determine: the significant influence of understanding Sharia economics on the level of religiosity and awareness of paying ZIS. The significant effect of ease of digital access on the level of religiosity and awareness of paying ZIS. The significant effect of religiosity on awareness of paying ZIS. Religiosity significantly mediates the effect of understanding the Sharia economy on awareness of paying ZIS. Significant religiosity mediates the effect of ease of digital access on awareness of paying ZIS. This research is an expansion research with a quantitative approach. The research sample of 83 was taken from the population of FEBI IAIN Pontianak students in 2020, totalling 485 students. The analysis used is SEM-PLS using the Warp-PLS 8.0 programme. There is a significant effect of understanding Islamic economics on awareness of paying ZIS mediated by religiosity with a P-value of 0.005. There is no significant effect of ease of digital access on awareness of paying ZIS mediated by religiosity with a P-value of 0.117.